The factors affecting the demand of affordable housing among middle income groups in Ipoh, Perak / Sharifah Nor Iswani Syed Mohd Hashim - Syed Mohd Hashim, Sharifah Nor Iswani (2023)
Housing affordability in Malaysia is determined by the Median Multiple and DownMarket Penetration, with the median cost of housing being less than three times the median household's annual income. However, the housing affordability ratio has consistently been above three times in recent decades, as evidenced by data from NAPIC. The primary definition of affordable housing is the ability of one's salary to support the cost of buying a home. The government has introduced affordable housing schemes, such as the 11th Malaysian plan, to help M40 and 840 groups. However, the housing market in Malaysia faces challenges in meeting the demand for affordable housing, particularly among low- and middle-income households. The lack of adequate housing for M40 families in urban areas remains a concern, as they are often the target of public housing programs. Despite the increase in housing costs, M40 households are ineligible for low-cost housing. The government has introduced affordable housing schemes like the Home Ownership Program and Residensi Wilayah Keluarga Malaysia, but many of these schemes do not cater to the needs and lifestyles of middle-income buyers. Previous studies have mainly focused on the supply and demand of affordable houses for urban middle-income groups, neglecting decision-making factors among middle-income groups when purchasing housing schemes provided by the government.